2015 IFIP/IEEE International Symposium on Integrated Network Management (IM) 2015
DOI: 10.1109/inm.2015.7140464
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficient and latency aware TDM-PON for local customer internetworking

Abstract: Abstract-In this paper, we propose a novel energy efficient solution for TDM Passive Optical Networks (TDM-PONs), which is a widely used access network technology, to facilitate local customer internetworking. Here, our prime objectives are to ensure traffic latency among different customers connected through TDM-PON and maximize energy saving performance of Optical Network Units (ONUs), which are TDM-PON equipment situated at customer premises. To do so, we devise a novel sleep management protocols for ONUs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…On the other hand, the authors of [30,31] identified that optical access networks can be useful in the next few decades to support edge computing technologies. In [32], the authors studied the performance of centralized and decentralized bandwidth allocation algorithms in a long-reach optical access network to investigate the feasibility of computation offloading to edge-computing servers and develop an analytical framework to validate against simulated results.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, the authors of [30,31] identified that optical access networks can be useful in the next few decades to support edge computing technologies. In [32], the authors studied the performance of centralized and decentralized bandwidth allocation algorithms in a long-reach optical access network to investigate the feasibility of computation offloading to edge-computing servers and develop an analytical framework to validate against simulated results.…”
Section: Related Workmentioning
confidence: 99%
“…We evaluate their performance results using our outstanding TDM-PON OPNET Modular based simulator model (this model presented in [12] and used in [8], [22]). For performance evaluation, we assume that the OLT assigns always a fixed sleep interval period T s for an ONU similar to [11].…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Passive optical network (PON) technology is considered to be one of the ideal choices for network operators for expanding their footprints in access network segments because PON technology introduces several benefits including high scalability, rich bandwidth capacity, cost-effective services and relatively low energy consumption compared to other access network technologies [1], [2]. Due to wide penetration of mobile devices and stupendous growth of rich Internet applications, PON is considered to be an ideal choice as backhaul for wireless access segment.…”
Section: Introductionmentioning
confidence: 99%